One-week inpatient cognitive behavioral therapy for insomnia: a retrospective study - Cai, Qing; Li, Mengya; Li, Guifeng; Xu, Xin; Li, Cheng; Li, Qifang (Frontiers in Psychiatry, 2024)
Objective To examine the effectiveness of one-week inpatient cognitive behavioral therapy for insomnia (CBT-I) in patients without severe mental disorders in the real-world setting to answer the research question “Can inpatient CBT-I be abbreviated?”. Methods In this retrospective, single-group, pretest–posttest study, the clinical outcome data of 94 patients who underwent one-week inpatient CBT-I were collected. Self-report scale scores and hypnotic medication use were obtained at baseline and at the 3-month follow-up after therapy. Results CBT-I significantly improved insomnia severity (Z = −7.65, P < 0.001, Cohen’s d = 1.34), anxiety (Z = −6.23, P < 0.001, Cohen’s d = 1.02), depression (Z = −6.42, P < 0.001, Cohen’s d = 1.06), daytime sleepiness (Z = −2.40, P = 0.016, Cohen’s d = 0.35), and fatigue severity (Z = −5.54, P < 0.001, Cohen’s d = 0.88) and reduced hypnotic medication use (χ2 = 33.62, P < 0.001). At the follow-up assessment, 58 patients (67.4%) had clinically meaningful changes in insomnia, and 51 patients (59.3%) met the criteria for insomnia remission. Conclusion The results of this preliminary study imply that one-week inpatient CBT-I may be an effective intervention for the treatment of insomnia in patients without severe mental disorders.